Colorless to Purple–Red Switching Electrochromic Anthraquinone Imides with Broad Visible/Near‐IR Absorptions in the Radical Anion State: Simulation‐Aided Molecular Design. Issue 7 (29th April 2013) - Chen, Fengkun; Zhang, Jie; Jiang, Hong; Wan, Xinhua
Abstract The large redshift of near‐infrared (NIR) absorptions of nitro‐substituted anthraquinone imide (Nitro‐AQI) radical anions, relative to other AQI derivatives, is rationalized based on quantum chemical calculations. Calculations reveal that the delocalization effects of electronegative substitution in the radical anion states is dramatically enhanced, thus leading to a significant decrease in the HOMO–LUMO band gap in the radical anion states. Based on this understanding, an AQI derivative with an even stronger electron‐withdrawing dicyanovinyl (di‐CN) substituent was designed and prepared. The resulting molecule, di‐CN‐AQI, displays no absorption in the Vis/NIR region in the neutral state, but absorbs intensively in the range of λ=700–1000 (λmax≈860 nm) and λ=1100–1800 nm (λmax≈1400 nm) upon one‐electron reduction; this is accompanied by a transition from a highly transmissive colorless solution to one that is purple–red. The relationship between calculated radical anionic HOMO–LUMO gaps and the electron‐withdrawing capacity of the substituents is also determined by employing Hammett parameter, which could serve as a theoretical tool for further molecular design.